Evaluation of meat characteristics of West African dwarf rams fed graded levels of fungal treated maize cobs (2015)
An experiment was conducted to determine the impact of fungal treated maize cob (FTMC) used as supplement on the carcass characteristics of West African dwarf (WAD) ram. Maize cob treated with Pleurotus tuber reguim was supplemented at 0, 10, 20, 30 and 40% w/w to complete feed mixtures (CFM). A total of 20 grower rams with an average age of ten months were selected for the evaluation of carcass characteristics. The animals were starved of feed for 16 hours, weighed, stunned, slaughtered and properly bled. The thoroughly bled carcass were dressed and eviscerated. The dressed carcass were cut into half carcasses, left half was dissected to determine internal offal while the other half was cut into primal cuts: neck, rack, loin, flank and leg. The final body weight (27.33kg), mean weight gain (11.58kg), rib eye area (10.70%) and dressing percentage (50.11%) were significantly better far rams on treatment 5 and in general all rams on FTMC supplemented diets compared with the control. Similarly hot carcass weight increased with supplementation from 9.55kg (T)) to 11.99kg (T2). Variations in rack and kidney weights as affected by treatments was not significant (P>0.05). Treatment effect on shoulder weight was significant (P<0.05) far animals on FTMC compared with the control groups. However, no significant (P>0.05) differences was observed far those 011 diets 3, 4 and .5 It can be concluded from the results obtained in this experiment that WAD rams fed FTMC improve the dressing percentage and rib eye area without any noticeable detrimental effect on the organ parts.